Zoonotic transmission of the Mycobacterium tuberculosis complex between cattle and humans in Central Ethiopia - Woldemariam, Tefera; Mohammed, Temesgen; Zewude, Aboma; Chanyalew, Mahlet; Khalifa, Hazim O.; Mamo, Gezahegne; Ameni, Gobena (Frontiers in Veterinary Science, 2025)
IntroductionThe zoonotic transmission of tuberculosis (TB) from cattle to humans has long been recognized, while the reverse transmission from humans to animals has only recently been reported. The socioeconomic conditions in rural Ethiopia are conducive to the zoonotic and reverse zoonotic transmission of TB between cattle and humans. This study aimed to explore the transmission of the Mycobacterium tuberculosis complex between cattle and humans in Central Ethiopia.MethodsTo achieve this objective, a cross-sectional study was conducted involving 1,896 cattle slaughtered at two abattoirs and 392 human subjects suspected of tuberculosis who visited health institutions for treatment. Mycobacteriological culture and spoligotyping were used for the study. Additionally, the Spoligotype International Types and VNTR (variable number of DNA tandem repeats) International Types (SITVIT2) database and the online tool “Run TB-Lineage” were used to identify SIT and lineages of the isolates from both humans and cattle.ResultsCulture positivity was found in 26.3% (21/80) of the gross TB-suspicious tissue lesions in the lungs and lymph nodes (mandibular, retropharyngeal, cranial, and caudal mediastinal, as well as left and right bronchial, hepatic, and mesenteric lymph nodes) of cattle. Of the 21 cattle isolates, 12 (57.2%) were identified as M. bovis, while the remaining 9 (42.8%) were classified as M. tuberculosis. Similarly, only 22% (86/392) of the sputum samples from TB-suspicious humans were culture positive. These 86 human isolates included 81 M. tuberculosis, three M. africanum, and two M. bovis, as determined by spoligotyping. SIT50, SIT118, and SIT1318, which belong to the human species, were isolated from both humans and cattle. The two human M. bovis isolates exhibited the pattern of SB1443, which was not identified in cattle within this study area.ConclusionThe zoonotic and reverse zoonotic transmissions of TB were confirmed in Ethiopia by isolating two M. bovis from humans and nine M. tuberculosis from cattle, which suggested a greater role for M. tuberculosis in cattle compared to M. bovis in humans.